Potential Mislejk on Authority to Creditors Previously with the Debtor to Apply for the Elimination or Deletion of Mortgage Associated with the Mortgage Law and the Ministerial Regulation on Electronic Mortgage Rights (HT-EL) - Erni Rohaini; A. Harits Nu’man; Dini Dewi Heniarti; Neni Ruhaeni (International Journal of Science and Society, 2022)
The purpose of this study was to analyze the potential of Mislejk on the authority to creditors to abolish mortgage rights. The research method in writing this article is normative juridical. Secondary legal sources are used as the main sources in this study which are then processed to identify the main issues in positioning legal rules or norms as the basis for the author's assessment, taking into account some primary and tertiary legal materials. Based on the analysis, it can be concluded that the provisions of Article 22 paragraph (6) of the Mortgage Law as previously described do not have legal certainty. Thus, legal remedies that can be taken by the Customer in resolving Creditors who are reluctant to write off are as follows: Internal Settlement through the Banking Law mechanism, Settlement through Alternative Dispute Resolution, and Settlement through Courts.